2019
DOI: 10.1111/lam.13097
|View full text |Cite
|
Sign up to set email alerts
|

Arabinoxylan from Argentinian whole wheat flour promote the growth of Lactobacillus reuteri and Bifidobacterium breve

Abstract: Arabinoxylans are part of dietary fibre and have received attention given their emergent prebiotic character. Four arabinoxylans extracts were obtained from Argentinian soft and hard wheat. In vitro assays were performed to describe the extent to which the extracts from whole wheat flour support selective growth of Bifidobacterium breve and probiotic Lactobacillus reuteri ATCC23272 in a defined media. The prebiotic effect was evaluated by three quantitative scores: relative growth, prebiotic activity score and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
(57 reference statements)
2
13
1
Order By: Relevance
“…Crittenden et al [18] found that B. longum is more efficient than Bacteroides strains when using AX as a growth substrate. Additionally, evident growth of Bifidobacterium breve 286 on wheat AX was observed by Paesani et al [27]. The degradation of AX by Bifidobacteria was demonstrated to be strain-dependent [28] and susceptible to cross-feeding between two strains, as previously reported with B. longum and B. adolescentis [14].…”
Section: Ax Fermentationsupporting
confidence: 71%
“…Crittenden et al [18] found that B. longum is more efficient than Bacteroides strains when using AX as a growth substrate. Additionally, evident growth of Bifidobacterium breve 286 on wheat AX was observed by Paesani et al [27]. The degradation of AX by Bifidobacteria was demonstrated to be strain-dependent [28] and susceptible to cross-feeding between two strains, as previously reported with B. longum and B. adolescentis [14].…”
Section: Ax Fermentationsupporting
confidence: 71%
“…arabinoxylan [corn, wheat], beta glucan [oat], cellulose [corn, alfalfa, wheat, beet], hemicellulose [corn, alfalfa, wheat, beet], pectin [beet] [55][56][57][58]. These different dietary fibers have been shown to serve as nutrient sources for a variety of gut microbial taxa, including the genus Bifidobacterium (cellulose, pectin, oat, arabinoxylan) [59][60][61][62][63], the genus Parasutterella (pectin) [63], the phylum Actinobacteria (pectin) [63], and the genera Bacteroides-Prevotella (oat, arabinoxylan) [59], among others. The present study was not designed to pinpoint the effects of specific dietary fibers (or lack thereof) on cognitive function or the microbiome, but this is an important area of future work.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that these “good” commensals can become “bad” and can cause unwarranted immune stimulation in genetically susceptible individuals reiterating the likely effect of host genetics on microbiome composition. Other than host genetics, differential selection pressure through diet 42,43 ; disease characteristics; and persistent use of 5-ASA (which changes the colonic luminal pH and hence promote growth of Bifidobacterium and Lactobacillus) 35 , could be the non-genetic factors that may have contributed on the gut microbial assemblage. Considering the global uniformity of treatment modalities it seems that effect of disease modifying drugs on expansion of these genera is minimal.…”
Section: Discussionmentioning
confidence: 99%